Predictive findings of allergic disease in fiberoptic nasolaryngoscopy. (14th August 2014) - Brook, Christopher; Noordzij, J. Pieter; Russell, Kimberly; Aliphas, Avner; Platt, Michael
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis To determine whether findings on fiberoptic nasolaryngoscopy beyond the nasal cavity can aid in diagnosis of atopy. Study Design Case control analysis of patients undergoing fiberoptic nasolaryngoscopy and allergy testing at a single academic institution. Methods Patients who underwent flexible nasolaryngoscopy for either laryngeal or nasal symptoms and allergy testing by in vitro methods were divided into an atopic group and a nonatopic control group based on results of allergy testing. Three board‐certified otolaryngologists who were blinded to the atopic status and symptoms viewed 88 patient videos and filled out an 8‐item endoscopic rating questionnaire for each. Correlation between rater scores, endoscopic findings, and atopic status was calculated using Randolph's multirater kappa values and Mann‐Whitney test. Results Intrarater reliability was moderate to perfect for all physicians on all questions (kappa 0.545–1.0). Inter‐rater reliability was slight to fair (kappa 0.143–0.399) for all questions and the overall impression of atopic disease. Abnormalities of the torus tubarius (P = .007) and increased nasopharyngeal secretions (P = .038) were predictive of atopic disease, whereas the presence of an adenoid (P = .08) and impression of atopic disease (P = .15) approached significance. All other endoscopic measures were not predictive of atopic status. Conclusions Fiberoptic nasolaryngeal findings within the nasopharynx rather than the larynx are predictive of a positive atopic status. Level of Evidence 3b. Laryngoscope, 125:286–290, 2015